The Potential Role of Melatonin on Memory Function: Lessons from Rodent Studies - Zakaria, Rahimah; Ahmad, Asma Hayati; Othman, Zahiruddin (Charles University - First Faculty of Medicine, 2016)
Pineal melatonin biosynthesis is regulated by the circadian clock located in the suprachiasmatic nucleus of the hypothalamus. Melatonin has been found to modulate the learning and memory process in human as well as in animals. Endogenous melatonin modulates the process of newly acquired information into long-term memory, while melatonin treatment has been found to reduce memory deficits in elderly people and in various animal models. However, the mechanisms mediating the enhancing effect of melatonin on memory remain elusive. This review intends to explore the possible mechanisms by looking at previous data on the effects of melatonin treatment on memory performance in rodents.